Calculus

posted by .

Let f(x) = -2/((5+3x)^4)

Determine f'(x) using the chain role.

Can someone please do this step by step and explain?

  • Calculus -

    first change it to
    f(x) = -2(5+3x)^-4

    f'(x) = -8(5+3x)^-5 (3)
    = -24(5+3x)^-5 or -24/((5+3x)^5)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Calculus--complex numbers

    let z= a+bi be a complex number. it is given that the quotient (z-i)/(z-1) is purely imaginary. show that z lies on a circle and determine the centre and radius of this circle. OK, here's my working out...( i am using "X" as my times …
  2. Calculus

    Find the equation of the tangent to the curve y=2-e^-x at the point where x=1. Can someone please do this step by step and explain?
  3. Algebra help

    f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this?
  4. AP Calculus - High School

    The Temperature T of food put in a freezer is T = (700) / t^2+4t+10 where t is the time in hours. Find the rate of change of T with respect to t at each of the following times. a. t=1 b. t=3 c. t=5 d. t=10 ** i'll be able to do the …
  5. Calculus

    I need step by step help with the chain rule for this problem: 7(x^(7/3)+(11/7)x^(7/5)+13x^(7/7))^(4/3)
  6. Physics

    Can someone please show me step by step how to normalize e^-5x in the interval (0, infinity)?
  7. Algebra 1--Step-by-Step

    Can someone show me how to solve these step-by-step?
  8. Chemistry

    In a chain mechanism, a reaction in which two free radicals combine to form a stable molecule would be called the A) initiation step B) termination step C) propagation step D) inhibition step E) branching step
  9. Math

    I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 − …
  10. Math Help

    An equation is shown below: 4(2x - 5) + 15 = 11 Write the steps you will use to solve the equation and explain each step. Can someone please explain step by step this equation?

More Similar Questions